The Aqidah Education in Ahlu Sunnah wa al-Jamaah: A Comparative Study - Arifudin, Yadi Fahmi (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2022)
Tebuireng and Al Irsyad are two of Indonesia's largest Islamic boarding schools. Both are schools of Ahlussunnah wal Jama'ah but with different madzhab. This study aimed to discover the similarities and differences in the concept of aqidah education beetwen Tebuireng and al Irsyad islamic boarding school. This research used a descriptive qualitative method. The data were collected by using observation, interviews, and documentation. The results of this study show similarities in objectives, including students' abilities and competencies. Two schools expected students to have thoughts and aqidah according to the teachings of the Ahlusunnah wal Jama’ah. Yet, to be a person who has good morals (akhlaqul karimah). The similarities in teaching materials that serve as learning guidelines include the Al-Quran and the book of Sahih Bukhari Hadith, whereas in learning methods include lecture, discussion, question and answer methods, sorogan, bandongan, assignments, demonstrations/performance, habituation, reward, and punishment. The assasment methods include formative, sub-formative and summative exams in oral-writing exams and to assess behaviour using observation and journal methods. The difference in purpose lies in the attitude towards the input and output of the students. Tebuireng Islamic Boarding School emphasizes the preservation of religious traditions. While Al Irsyad Islamic Boarding School emphasizes implanting new understandings but is still based on the most authentic sources; Al Quran and sunnah. The difference in teaching materials in the yellow book, while The difference in evaluation is that the Tebuireng Islamic Boarding School emphasizes mastery of the religious traditions of the Ghairu Mahdzah. In contrast, the Al Irsyad Islamic Boarding School emphasizes the Mahdhah.